Oltre lo specchio: Lacan e Merleau-Ponty - Sili, Gioia (B@belonline, 2020)
The theory of the ‘mirror stage’, developed within many years by the psychoanalyst Jacques Lacan, was then taken up by the philosopher Maurice Merleau-Ponty in several times. The value of this reflection is so deep that nowadays it still represents an open field of research. In this regard, the paper intends to highlight, from a critical point of view, the different interpretations followed over time, paying particular attention to the relationship between screen and subject. At the same time, several common elements in the two authors will be focused.